Separation and Determination of Salidroside, Caffeic Acid and Gallic Acid in Rhodiola L. by Large-Volume Sample Stacking-Sweeping-Micellar Electrokinetic Chromatography - Huang, Wen-Yi; Li, Li-Jun; Hu, Da-Chun; Wu, Mei-Yan; Gao, Wen-Yan; Lai, Ying-Biao; Li, Yan-Qing (Asian Journal of Chemistry, 2012)
In this study, a new method for simultaneous determination of salidroside, caffeic acid and gallic acid in Rhodiola L. by large volume sample stacking-Sweeping micellar electrokinetic chromatography (LVSS-sweeping-MEKC) has been proposed. The determination conditions containing pH in background solution, concentrations of Na2B4O7, sodium dodecyl sulfate (SDS) and acetonitrile, injection time, negative voltage and separation voltage were optimized. The operating buffer was composed of 20 mmol/L Na2B4O7, 80 mmol/L sodium dodecyl sulfate and 10 % (by volume) acetonitrile at pH 9.7 with a constant temperature of 25 ºC. The UV detection wavelength was 213 nm, the reverse voltage was -8 kV, separation voltage was 20 kV and injection time was 120 s. The linear ranges of the method were 13.1-49.6 μg/L for salidroside, 1.0-15.7 μg/L for caffeic acid and 1.1-18.2 μg/L for gallic acid. The recoveries were 95-106, 98-112 and 91-108 %, respectively. The RSDs of peak area were less than 4 % and detection limits (S/N = 3) were 194, 28 and 29 μg/L for salidroside, caffeic acid and gallic acid respectively.